A questão urbano-habitacional em Cuiabá - MT : uma análise dos efeitos da localização dos conjuntos habitacionais no período 1960 a 2010 - Biancardini Filho, Ary (2014)
In Brazil, the demand for social housing is one of the serious problems to be resolved, and how this issue is addressed nowadays became one of the main factors influencing the evolution of the urban perimeter of our cities. In the city of Cuiabá, this urban expansion occurred intensively and often without adequate planning especially during the 60's and as a consequence a number of deficiencies in urban infrastructure. The deficiency or lack of this basic infrastructure eventually lead to various obstacles and difficulties to the full development of social, economical and environmental activities, and the local population's quality of life. Thus, the city of Cuiabá comes to present days suffering many consequences of vertiginous and disorderly urban sprawl. This study aims to analyze, through literature and documents' search, how the housing programs of the federal, state and municipal governments were implemented in the city of Cuiabá and how the evolution of its urban perimeter happened. From this analysis it was found how low income housing sections of the population influenced the urban expansion of the city and how this process has generated a number of shortcomings in relation to infrastructure. The analysis of this rarefied and disordered growth process and its consequences for the municipality, may contribute to the municipal, executive and legislative powers, in the sense that different actions are adopted viewing the urban density with a consequent optimization of the urban infrastructure.